Effects of Including Information about Hidden Hearing Loss in an Adopt-A-Band Program on College Band Members' Attitudes toward Healthy Hearing Behaviors - Seever, Katie L.; Johnson, Carole E.; Baldwin, Jonathan; Danhauer, Jeffrey L.; Wolfe, Brian; Jeannont, Stevana (Seminars in Hearing, 2018)
Young musicians may be at risk for developing cochlear synaptopathy (CS), or hidden hearing loss (HHL), that could lead to permanent music-induced hearing loss (MIHL). Patients with CS often complain of tinnitus and/or difficulty understanding speech in noisy situations, even though traditional audiometric testing indicates normal hearing. The aim of this article was to determine the effects of including information about HHL on an Adopt-A-Band program involving college band members' concern about and self-efficacy toward the prevention of MIHL. We conducted a single-blinded, randomized clinical trial. Forty-eight band members participated in this study. Band members were randomly assigned to two Adopt-A-Band presentations, one with and one without information on HHL. Including information about HHL had no effect on these band members' concerns about and self-efficacy toward the prevention of MIHL. However, the Adopt-A-Band program resulted in significantly increased concern for MIHL by 39.5% (p < 0.0001, 95% confidence interval [CI]: 25–54.2), self-efficacy in its prevention by 79.1% (p < 0.0001, 95% CI: 66.9–91.2), and plans to use musicians' earplugs while playing by 67.4% (p < 0.0001, 95% CI: 53.4–81.45). Although inclusion of information about HHL did not have a significant effect, the Adopt-A-Band program, in general, significantly increased the immediate intent of these students to practice healthy hearing behaviors. Future research is needed to determine the long-term effects of using the Adopt-A-Band program with university marching bands' use of healthy hearing behaviors.
Keywords: cochlear synaptopathy; hearing conservation; hidden hearing loss; music-induced hearing loss